Pelayanan Pastoral Dengan Aspek-Aspeknya di Gereja Bethel Indonesia Jemaat Sungai Yordan Surabaya - Fatony Pranoto; Ivonne Eliawaty; Surja Permana (Jurnal Teologi dan Pelayanan Kerusso, 2018)
Pastoral service is a spiritual service and should not be ignored in the pastoral ministry. At GBI the Jordan River Surabaya has provided several models of material services: Money / goods to help congregations in need; Spiritually: introducing people to Jesus Christ and to life in the Holy Spirit or led by the Spirit, new born life becomes a new creation (not only identity / without repentance; Healing: making others healthy, both physical, mental and emotional as well as; Prophetic: changing the way of human life in the structure of society. Improve people’s way of life (especially in rural areas).